Psychological Contract Fulfillment on Employees Reactions within the Context of Organizational Justice - Abdul Khaliq; Kashif Mehmood; Aamir Zamir Kamboh; Kainat Durrani; Muhammad Haidar Zarar; Shaheen Nazar (SEISENSE (PRIVATE) LIMITED, 2019)
Aim - The objective of the study was to examine the psychological contract expectations by employees and the impact of any deviation from its perceived benefits by the employees of an organization, as they occur within social exchange relationships to account for employee responses. Methodology - This is an exploratory longitudinal study in which an investigation is made into the changes in employment obligations as perceived by employees based on the level of fulfillment of contract obligations by their employer(s). Findings - It was deduced that an employer's inability to fulfill its contractual commitments was the foundational cause associated with the decline in cooperation of the employees to fulfill their employment obligations. Significance - The results of the current study show that there is a significant and positive relationship between Psychological Contract Fulfilment and Employee Reaction. Results presented that there is a significant and positive relationship between Organizational Justice and Employee Reaction. Results presented that there is a significant and positive relationship between Organizational Justice and Psychological Contract Fulfilment.